Extraordinary Times Require Extraordinary Action: Boosting European Demand by Means of Investment Helicopter Money - Thomas Gries; Alexandra Mitschke (Credit and Capital Markets – Kredit und Kapital, 2021)
This theoretical contribution analyzes remaining monetary policy tools and their ability to reestablish sound macroeconomic conditions in the euro area. Motivated by the observation of a lack of investment in the macroeconomy and subdued inflation, we review current monetary policy challenges and emphasize the major failure of traditional transmission channels. While interest rates and asset prices often respond to central bank tools, the effects on the real economy, specifically on investments, are often not observable. We suggest Investment Helicopter Money as a tool to directly strengthen investment and boost aggregate demand. This monetary impulse is found to offer a direct real effect without crowding-out investment or rising debt levels. Most importantly, we discuss necessary institutional arrangements and contrast the suggested tool with a simple monetary or fiscal impulse.
Keywords: G1; H54; E42; E52; E61; 330; Monetary Systems; Monetary Policy; Policy Coordination; Investment Decisions; Infrastructures; Other Public Investment and Capital Stock